Four and a Half LIM Domains Protein 2 Mediates Bortezomib-Induced Osteogenic Differentiation of Mesenchymal Stem Cells in Multiple Myeloma Through p53 Signaling and β-Catenin Nuclear Enrichment - Xie, Zhenqing; Xu, Yan; Wei, Xiaojing; An, Gang; Hao, Mu; Yu, Zhen; Qiu, Lugui (Frontiers in Oncology, 2021)
Myeloma bone disease (MBD), caused by the inhibition of osteoblast activity and the activation of osteoclast in the bone marrow environment, is the most frequent and life-threatening complication in multiple myeloma (MM) patients. Bortezomib (Bzb) was shown to promote MM-derived mesenchymal stem cells (MM-MSCs) differentiation to osteoblast in vitro and in animal models, promoting the bone formation and regeneration, may be mediated via β-catenin/T-cell factor (TCF) pathway. Further defining molecular mechanism of Bzb-enhanced bone formation in MM will be beneficial for the treatment of myeloma patients. The present study has identified for the first time four and a half LIM domains protein 2 (FHL2), a tissue-specific coregulator that interacts with many osteogenic marker molecules, as a therapeutic target to ameliorate MM bone disease. First, increased messenger RNA (mRNA) and protein levels of FHL2, and the mRNA level of main osteoblast markers (including Runx2, ALP, and Col1A1), were found in MM-patients-derived MSCs after Bzb treatment. FHL2 KD with short hairpin RNA (shRNA) reduced the expression of osteoblast marker genes and blocked the osteogenic differentiation of MM-MSCs regardless of the presence or absence of Bzb, implying that FHL2 is an important activator of the osteogenic differentiation of human MSCs under a proteasome inhibition condition. Molecular analysis showed that the enhanced expression of FHL2 was associated with the Bzb-induced upregulation of p53. No significant change at protein level of total β-catenin was observed with or without Bzb treatment. However, it was mostly enriched to nuclei in MSCs after Bzb treatment. Moreover, β-catenin was restricted to the perinuclear region in FHL2 KD cells. These data provide evidence that FHL2 is essential for promoting β-catenin nuclear enrichment in MM-MSCs. In conclusion, FHL2 is critical for Bzb-induced osteoblast differentiation of MM-MSCs and promotes the osteogenesis, through p53 signaling and β-catenin activation. Targeting FHL2 in MM may provide a new therapeutic strategy for treating MBD.